2010
DOI: 10.1007/s10509-010-0445-4
|View full text |Cite
|
Sign up to set email alerts
|

A class of charged analogues of Durgapal and Fuloria superdense star

Abstract: A class of charged analogues of superdense star model due to M.C. Durgapal and R.S. Fuloria, is obtained by using a particular electric field, which involves a parameter K. The members of this class are seen to satisfy the various physical conditions e.g. c 2 ρ ≥ 3p ≥ 0, dp/dr < 0, dρ/dr < 0, along with the velocity of sound condition dp/c 2 dρ < 1 and the adiabatic index ((p + c 2 ρ)/p)(dp/(c 2 dρ)) > 1 for the interval 1 < K ≤ 1.73 with the maximum mass 3.2860 M and the radius 18.3990 km.It is interesting to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…In connection to anisotropy we note that it was Ruderman [6] who argued that the nuclear matter may have anisotropic features at least in certain very high density ranges (>10 15 gm/cm 3 ), and thus the nuclear interaction can be treated under relativistic background. Later on Bowers and Liang [7] specifically investigated the non-negligible effects of anisotropy on the maximum equilibrium mass and surface redshift.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In connection to anisotropy we note that it was Ruderman [6] who argued that the nuclear matter may have anisotropic features at least in certain very high density ranges (>10 15 gm/cm 3 ), and thus the nuclear interaction can be treated under relativistic background. Later on Bowers and Liang [7] specifically investigated the non-negligible effects of anisotropy on the maximum equilibrium mass and surface redshift.…”
Section: Introductionmentioning
confidence: 86%
“…They showed that the model in connection to the neutron star stands all physical tests with the maximum mass 4.17 M and the surface redshift 0.63. Very recently, Gupta and Maurya [3] presented a class of charged analogs of the superdense star model due to Durgapal and Fuloria [1] with Einstein-Maxwell spacetimes. The members of this class have been shown to satisfy various physical conditions and exhibit these features: (a) a maximum mass 3.2860 M and a radius 18.3990 km for a particular interval of the parameter: 1 < K ≤ 1.7300, and (b) a maximum mass 1.9672 M and a radius 15.9755 km for another interval of the parameter: 1 < K ≤ 1.1021.…”
Section: Introductionmentioning
confidence: 99%
“…(iv) It is seen that the physical parameters like total mass, radius, mass to radius ratio, total charge to total mass ratio, central red shift and surface red shift increases with increasing β 1 (or f 0 ) and u, and decreasing L. (v) Interestingly, red-shift, velocity of sound and p/c 2 ρ are monotonically decreasing towards the pressurefree surface while adiabatic index is monotonically increasing. The velocity of sound and the ratio p/c 2 ρ monotonically decreasing towards the surface are also possessed by the uncharged model, Knutsen (1989) and charged model, Gupta and Maurya (2010). Energy density ρ and pressure p from (3.7) and (3.8) can be expressed in terms of parameters L and β 1 on using f 0 = 1+β 1 2R 2 and f a = (3L − 2)/(2R 2 ) from (2.5) and (3.5) respectively.…”
Section: Numerical Values Of Physical Quantitiesmentioning
confidence: 97%
“…, [(n = 1) Tolman's IV (n = 2) Adler (1974), Heintzmann (1969), (n = 4, 5) Durgapal (1982), Gupta and Maurya (2010a), (n = 6) Pant et al (2010b)] Only solution by Gupta and Maurya (2010a) has well behaved neutral counterpart = e nω = e n(c 1 +c 2 r 2 ) Z =…”
Section: Physical Analysis Of the Solutionsmentioning
confidence: 99%